Merdeka Belajar: A Study of the Pros and Cons for Education in Indonesia - Abidarda, Yulizar; Haryadi, Rudi (Medan State University, 2024)
This research aims to examine a number of literature that discusses the pros and cons of the Merdeka Belajar policy which has been implemented since the end of 2020. The research method in this article uses a systematic literature review. Eighteen key articles were obtained from the selection of a total of 836 scientific article titles obtained from the Google Scholar database. Eighteen articles were studied systematically to obtain conclusions regarding the pros and cons of the Merdeka Belajar policy. The research results found that the Merdeka Belajar policy, although considered a breakthrough in the millennial era, is not free from pros and cons. Some of the advantages are that it is simpler and deeper, more independent, more relevant and interactive, and more humane to students and educators. Meanwhile, the weaknesses that have become criticism of this policy include, among other things, the unpreparedness of technology, human resources, and the ineffectiveness of the Ministry's communication in grounding the concept of Independent Learning, resulting in misunderstandings in the field. It is recommended for readers to study more deeply the impact of the Merdeka Belajar policy for more specific fields of science, or for various institutions.